The culinary linguistic landscape of Kupang City, Indonesia: unraveling identity through sign boards - Naniana N. Benu; Budi A. Sudarmanto; Tri Wahyuni; Dian Susilastri; Erlinda Rosita; Amir Mahmud; Sri Yono (Cogent Arts & Humanities)
This study explores the culinary linguistic landscape of Kupang City, Indonesia, through an analysis of signboards in public spaces. Kupang, a multicultural and multilingual city, exhibits its diversity through the language choices on culinary signage, reflecting cultural identity, heritage, and modern influences. Using a qualitative approach, this research examines the linguistic of culinary signboards, focusing on language selection, cultural symbols, and visual design. Data were collected from 464 culinary signboards across various roads in Kupang. The findings reveal that while Indonesian dominates the signage, local and foreign languages also play significant roles in expressing authenticity and modernity. Culinary signboards function as cultural texts that connect the past and present, highlighting the interplay of tradition and globalization. This study contributes to the understanding of urban sociolinguistic dynamics and offers practical implications for preserving cultural diversity amidst modernization.